Measuring the Convergence/Divergence of “Serious Crime” Arrest Rates for Males and Females: 1960–1995 - O'Brien, Robert M. (Journal of quantitative criminology, 1999)
It is now almost a quarter of a century since Adler (1975) and Simon (1975)stimulated a debate about the convergence of crime rates for men andwomen. The ensuing debate generated literally dozens of papers. Given theexistence of a series that now extends from 1960 to 1995, this papersuggests an appropriate way to examine the convergence hypothesis usingtime series techniques. These techniques take into consideration the effectsof the following factors: (a) random “shocks” or“innovations,” (b) the potentially lasting effects of suchinnovations, and (c) the autocorrelation that time series oftenexhibit. Using time series techniques on annual data, we examine trends inthe arrest rates for males and females for six Part I crimes (homicide,robbery, aggravated assault, burglary, larceny, and motor vehicle theft)for the years 1960 through 1995. We test for convergence, divergence, notrend, and a special condition of equilibrium between series called cointegration .